Character traits of the individual women with different types of attachment to a partner. - Кочарян, Олександр Суренович; Барінова, Наталія Вікторівна; Свинаренко, Юлія Валеріївна (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2016)
The article investigates the character traits of personality of girls with different type of attachment to a partner. Study sample included women of youth age and early adulthood, in there were was established four types of attachment: “Autonomy”, “Pseudo-autonomy”, “Disorientation” and “Hyper-attachment”. The results show that among the groups of girls with broken attachment types there are significant differences in the expression of character traits. According to the results of the questionnaire Grygera who explores characterological traits of personality, the following factors have been shown, “Active I”, “Defender I”, “Conformal I”. There were also describedthe above factors, the psychological content.